2010
DOI: 10.1177/1934578x1000501229
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Volatile Oils of Aquilaria malaccensis (Thymelaeaceae) from Malaysia

Abstract: Volatile oils of Aquilaria malaccensis Benth. (Thymelaeaceae) from Malaysia were obtained by hydrodistillation and subjected to detailed GC-FID and GC/MS analyses to determine possible similarities and differences in their chemical composition in comparison with the commercial oil. A total of thirty-one compounds were identified compared with twenty-nine identified in the commercial oil. The major compounds identified were 4-phenyl-2-butanone (32.1%), jinkoh-eremol (6.5%) and α-guaiene (5.8%), while the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 7 publications
1
40
0
Order By: Relevance
“…It is worth noting that in publications dealing with agarwood, the term 'agarwood oil' is used more frequently than 'essential oil'. The motivation to study the compounds in oil is often related to the development of scientific grading and quality control for commercial applications (Ismail et al, 2014;Ismail et al, 2013;Tajuddin et al, 2013;Tajuddin and Yusoff, 2010). Variations in species and origin were also studied, as they are considered to be related to the oil quality (Hashim et al, 2014b;Nor Azah et al, 2008).…”
Section: Resin and Essential Oilmentioning
confidence: 98%
“…It is worth noting that in publications dealing with agarwood, the term 'agarwood oil' is used more frequently than 'essential oil'. The motivation to study the compounds in oil is often related to the development of scientific grading and quality control for commercial applications (Ismail et al, 2014;Ismail et al, 2013;Tajuddin et al, 2013;Tajuddin and Yusoff, 2010). Variations in species and origin were also studied, as they are considered to be related to the oil quality (Hashim et al, 2014b;Nor Azah et al, 2008).…”
Section: Resin and Essential Oilmentioning
confidence: 98%
“…This analysis extracted major volatile components such as sesquiterpenes and it is popular in market [9]. The studies on colour in oil volatile components has been carried out and they found that different colour has different chemical constituents [6,14]. For example, GC-MS chromathographed that oxidoagarochromone as a pale yellow in oil component [19].…”
Section: Introductionmentioning
confidence: 98%
“…However, standard agarwood oil quality is limited due to human nose cannot accept many samples in one time and easily get fatigues especially when dealing with continuous production [14]. The human sensory panel also limited in terms of subjectivity, poor reproducibility, time consumption and large labor expense [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, standard agarwood oil quality is limited due to human nose cannot accept many samples in one time and easily get fatigues especially when dealing with continuous production [7]. The human sensory panel also limited in terms of subjectivity, poor reproducibility, time consumption and large labor expense [8].…”
Section: Introductionmentioning
confidence: 99%